Being Outside the Decision-Loop: The Impact of Deep Brain Stimulation and Brain-Computer Interfaces on Autonomy - Monika Michałowska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
Recent advancements in new neural technologies raise bioethical concerns over personal autonomy, which they potentially threaten to diminish or entirely eliminate. Although caution in the application of deep brain stimulation (DBS) and brain-computer interfaces (BCIs) is explicitly urged in almost every study, the debate features a definitional void as to what notion of autonomy is actually adopted by the authors. The focus on autonomy has dominated the debate to such an extent that other essential values seem to be disappearing from the bioethical horizon, becoming less valued, less important, and less visible. This paper examines the autonomy-problem by probing whether DBS and BCIs indeed threaten personal autonomy. The impact of DBS and BCIs is studied on the examples of several illnesses, whereby the well-being of a person and the importance of informed consent are taken into account to assess the influence of these novel medical technologies on autonomy.